THE FEATURES OF INNOVATIVE ACTIVITY UNDER THE OPEN INNOVATION MODEL - Julia P. Kulikova (Статистика и экономика, 2016)
The article discusses the distinctive characteristics of open and closed models of functioning of the innovation sphere. Justified the use of interaction marketing approach to relationship management of innovation sphere. Two sets of marketing functions - network and process for the effective functioning of innovation networks. Given matrix scorecard marketing functions in the innovation network.